Production of pronoun gender by children acquiring Russian as a minority language: comparison with the effects of developmental language disorder - Elena Tribushinina; Pim Mak (University of Groningen Press, 2022)
This paper studies the acquisition of Russian pronominal gender by Dutch-Russian simultaneous bilinguals (4;3-7;11) growing up in the Netherlands. The performance of the bilingual group is compared to that of age-matched monolinguals with and without developmental language disorder (DLD). We hypothesize that reduced exposure to Russian in the minority-language context may lead to delays in language development, comparable to problems attested in DLD (in this case due to reduced intake). The results of a narrative elicitation task demonstrate that both monolingual groups performed at ceiling from age 4 onwards. Monolingual children with DLD were as accurate at using pronominal gender as their unimpaired peers from the earliest ages studied, which supports the processing accounts of DLD taking morphological richness of the target language into account. In contrast, 4-year-old bilinguals performed around chance level. The performance of the bilingual group improved with age and reached the monolingual level only by age 7. The results suggest that reduced input has more impact on the acquisition of gender in a morphologically rich language, whereas the possible effects of DLD are no longer visible after age 3.